How is the Readiness of Students to Become Teachers in the Industrial Revolution Era 4.0? - Rosmiati Rosmiati; Benar Sembiring; Arif Rahim; Wiwik Pudjaningsih; Zuhri Saputra Hutabarat (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This research intends to examine how students are prepared to become teachers in the industrial revolution 4.0 age in order to carry out teaching professionally and competently and produce the next generation of exceptional instructors. The methodology for this study is a quantitative survey model with 261 samples of students who have participated in teaching practice program activities and 755 populations. Furthermore, the data were analyzed using exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modeling (SEM). The research's first key result is that colleges have a crucial role to play in preparing teacher candidates for the industrial revolution 4.0 by enhancing education quality, distributing education fairly, and extending access via relevance. Second, by putting the study's theory to the test, students' perceptions of the teaching profession are improved. It may be inferred that students are more prepared to become teachers if learning techniques and models are combined in accordance with current trends in technology and society.